Press discourses on ecological crises in the UK, Israel, and Hungary - Yuval-Davis, Nira; Meier, Isabel; Rosen, Rolly; Varjú, Viktor (Frontiers in Sociology, 2023)
This article explores the relationships between political projects of belonging and approaches to environmental and climate ecological crises via comparing centre-right and centre-left newspapers in the UK, Israel and Hungary. Our theoretical framework draws on the politics of belonging (Yuval-Davis, 2011a) as a way of understanding and framing the different political projects that accompany reporting on ecological issues. Focusing on selected national and international case studies on these issues at the centre of public debate during the last two decades, the paper explores and compares these relationships by examining the eco-relational, spatial, temporal and normative framing dimensions of the political projects of belonging as expressed in these articles. The findings of the analysis show that, despite different cultural and historical contexts, the most significant dividing line is not among countries but between the different political projects of belonging of the newspapers. This can be seen even when dealing with country-specific, rather than international, case studies. Overall, centre-right newspapers tend to focus on narrow nationalist interests concerning the climate crisis and do not produce discourses of urgency to resolve the crisis except when reporting on major international political agendas. They are also more inclined to focus on the economic aspects of such efforts and how they would affect the ‘people’. The centre-left press, on the other hand, tends to prioritise ecological issues much more; it has wider global and planetary interdependent constructions of belonging and engages in the production of discourses of urgency in an attempt to solve the crisis and avoid future catastrophes. However, even in the centre-left press, especially in the UK, a tendency to remain within a western-centric perspective was observed.